SERVICE LOGISTICS CLASSIFICATION AND APPROACHES TO ITS EVALUATION (Marketing Journal, 2025)
This article consistently explores the content and essence of service logistics and highlights its main types: customer satisfaction service, production -related service, after-sales service, information service, and financial and credit service. Special attention is given to evaluation criteria for these types of service logistics, including delivery time and the “nomenclature and quantity” criterion.
Keywords: service logistics; customer satisfaction; after -sales service; delivery time; nomenclature and quantity criterion; financial and credit service